2019
DOI: 10.1007/s10654-019-00590-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk of intellectual disability in children born appropriate-for-gestational-age at term or post-term: impact of birth weight for gestational age and gestational age

Abstract: Children born small for gestational age have a higher risk of intellectual disability. We investigated associations of birth weight for gestational age percentile and gestational age with risk of intellectual disability in appropriate-for-gestational-age (AGA) children. We included 828,948 non-malformed term or post-term AGA singleton children (including 429,379 full siblings) born between 1998 and 2009 based on data from the Swedish Medical Birth Register. Diagnosis of intellectual disability after 3 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
2
21
0
1
Order By: Relevance
“…Consistent with our findings, increased risks of neonatal mortality, intellectual deficits, poorer school performance and long‐term neurological disorders have been found in children born at early term (37–38 weeks) 31–34 . Stillbirth risk increases with gestational age in term and especially post‐term pregnancies, and foetal growth restriction likely explains a part of this increased risk 35 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with our findings, increased risks of neonatal mortality, intellectual deficits, poorer school performance and long‐term neurological disorders have been found in children born at early term (37–38 weeks) 31–34 . Stillbirth risk increases with gestational age in term and especially post‐term pregnancies, and foetal growth restriction likely explains a part of this increased risk 35 .…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our findings, increased risks of neonatal mortality, intellectual deficits, poorer school performance and long-term neurological disorders have been found in children born at early term (37-38 weeks). [31][32][33][34] Stillbirth risk increases with gestational age in term and especially post-term pregnancies, and foetal growth restriction likely explains a part of this increased risk. 35 Among births at a specific gestational week, an approximate U-shaped pattern is evident in the gestational age-specific risks of stillbirth, infant mortality, CP and epilepsy, with the highest risks at 37 weeks and 42 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies are needed in the future. In addition, LBW is recognized to be driven from preterm-birth infants born with small-for-gestational-age at term or growth dysplasia born appropriate-for-gestational-age at term [25,29]. We found that preconception anemia induced a higher risk of LBW than SGA, and elevated Hb concentrations up to over 130 g/L were only associated with a statistically significant risk of LBW (adjusted RR:1.33, 95% CI: 1.08, 1.65) rather than SGA.…”
Section: Associations Between Preconception Hb Concentrations With Lbw and Sgamentioning
confidence: 99%
“…Gestational age at birth, specifically the gestational age in and of itself is independent of substance exposure, is an important factor in anticipating infant's medical risks and nursing care needs [15]. And the association between gestational age and cognitive impairment was observed in previous population analysis [16,17]. In previous studies, the gestational age at birth was shorter among the MAexposed infants compared to nonexposed infants in general.…”
Section: Gestational Agementioning
confidence: 99%